Delving into some specific features of the magnetic systems used for the plasma recycling of the spent nuclear fuel (SNF) - Yuferov, V.B.; Katrechko, V.V.; Vinnikov, D.V.; Tkachev, V.I.; Sorokina, D.D. (Вопросы атомной науки и техники, 2022)
Consideration was given to some specific issues of the development of magnetic systems intended for the SNF plasma separators to separate, extract and deposit the actinides and also to magnetic systems of a different purpose, in particular plasma source (PS), isotope separation system and low – temperature compensation system, including plasma jet (PJ) preparation system designed for the creation of an “umbrella-like” ion beam and for the film deposition in the “pocket”. Розглянуто деякі питання створення магнітних систем плазмових сепараторів ВЯП для розділення та вилучення осаджених актиноїдів. Також розглянуто магнітні системи для різного призначення: плазмового джерела (ПД), поділу ізотопів та низькотемпературної компенсуючої плазми, підготовки плазмового струменю ПД для створення «зонтичного» іонного пучка та осадження плівок у «кишені».